INCIDENCE OF SOMATIC DISEASES IN WOMEN WITH UTERINE AND BREAST HYPERPLASTIC DISEASES IN THE PERIMENOPAUSE - Askarova Zebo Zafarovna; Raximova Amira Oybekovna (Journals Park Publishing, 2023)
Analysis of anamnestic data revealed an increased level of somatic pathology in patients with uterine and mammary hyperplastic diseases, with a prevalence of cardiovascular and endocrine diseases. Thus, 97 (77.6%) women in the main group had cardiovascular disease and only one in five - 9 (22.5%) from the control group. Varicose vein disease was diagnosed in 87 (69.6%) against 7 (17.5%) in the control group. Hypertension was twice as common in patients with EH and BBC (12(9.6%) vs. 2(5%), respectively).